Scientific writing and communication papers, proposals, and presentations - Hofmann, Angelika H. 1965- (Oxford Univ. Press, 2014)
Covers all the areas of scientific communication that a scientist needs to know and to master to successfully promote his or her research and career. This unique "all-in-one" handbook begins with a discussion of the basics of scientific writing style and composition and then applies these principles to writing research papers, review articles, grant proposals, research statements, and résumés and to preparing academic presentations and posters. It is ideal for a wide range of readers, from upper-level undergraduates and graduate students to postdoctoral fellows, faculty, and professional researchers, in the life sciences, medicine, psychology, chemistry, and engineering.--Back cover
Includes bibliographical references (pages 701-704) and index
Scientific writing basics : style and composition -- Planning and laying the foundation -- Manuscripts : research papers and review articles -- Grant proposals -- Posters and presentations -- Job applications
Keywords: Communication in science; Scientific literature; Technical writing; Wissenschaftliches Manuskript; Veröffentlichung; Wissenschaftlicher Text; Wissenschaftliche Literatur; Wissenschaftskommunikation